THE EFFECT OF CURRENT RATIO, DEBT TO EQUITY RATIO, TOWARD RETURN ON ASSETS (CASE STUDY ON CONSUMER GOODS COMPANY) - Hantono, Hantono (Universitas Sam Ratulangi, 2018)
This study aims to detect the effect liquidity ratio, leverage ratio and profitability on consumer goods companies listing on the Indonesia Stock Exchange 2014 – 2017. The object of this study is all consumer goods companies listing on the Indonesia Stock Exchange which publishes audited financial statements for fiscal year 2014 – 2017, which amounted to 24 (twenty four) companies. The sampling technique is by using purposive sampling method where the sample is determined based on certain criteria determined by the researcher and has limitations in terms of generalization. The sample of research is 42 (forty two companies) Data collection method using documentation method Data analysis technique used is descriptive quantitative analysis using current ratio, debt to equity ratio and return on assets.